Occupational employment to 2005. - Silvestri, George T. (Monthly Labor Review)
Part of a special issue on Bureau of Labor Statistics (BLS) projections for the U.S. economy to the year 2005. The writer compares 1994–2005 projected changes in the structure of employment at the major occupational group level with the changes that took place from 1983 to 1994. He discusses the detailed occupations that are projected to grow the most quickly in percentage terms, those with the largest numerical increases, and those with the largest employment declines. In addition, he presents the total number of job openings that are expected to occur during the projections period as a result of growth in the economy and the net loss resulting from workers who leave the labor force or transfer to other occupations.